Metabolic Studies in Familial Hypercholesterolemia: EVIDENCE FOR A GENE-DOSAGE EFFECT IN VIVO - David W. Bilheimer (The Journal of Clinical Investigation, 1979)
To investigate the gene-dosage effect in familial hypercholesterolemia (FH), metabolic studies were conducted in a group of well-characterized patients with either heterozygous (n = 7) or homozygous (n = 7) FH and the results were compared to those obtained in normal subjects (n = 6). The turnover of 125I-labeled low-density lipoprotein (LDL) was measured in all of the normals, all but one of the FH heterozygotes, and in all of the homozygotes. Chemical cholesterol balance was performed simultaneously with the 125I-LDL turnover in all seven of the homozygotes. With regard to 125I-LDL turnover, FH homozygotes, who possess two doses of the mutant FH gene, exhibited a threefold increase in the rate of apoLDL synthesis while the fractional catabolic rate (FCR) for the apoprotein was only about one-third of normal. Heterozygotes, who have only one dose of the mutant FH gene, exhibited intermediate values for both parameters; that is, the FCR was two-thirds of normal and the apoLDL synthetic rate was 1.7-fold greater than normal. The data indicate that the single gene defect in FH produces two distinct abnormalities of LDL metabolism: (a) an increase in the synthetic rate for apoLDL and (b) a decrease in the efficiency of apoLDL catabolism. Both defects are more severe in FH homozygotes than in heterozygotes. The FCR for apoLDL in the homozygotes appeared to be fixed at ≅ 17%/d whereas the plasma LDL level varied about twofold. These findings suggest that the twofold variation in plasma LDL levels observed in these seven patients is caused by variation in the plasma apoLDL synthetic rates. Consistent with this conclusion was the finding that the correlation between the plasma LDL level and the apoLDL synthetic rates in the seven FH homozygotes was 0.943. The rate of total body cholesterol synthesis determined by chemical cholesterol balance did not appear to clearly differ between normals and patients with either one or two mutant FH genes. Two of the youngest FH homozygotes exhibited cholesterol overproduction but the other five did not. No consistent abnormality of bile acid metabolism was observed in these patients. Because the daily plasma flux of cholesterol on LDL is about threefold greater than the amount of cholesterol produced per day, a significant amount of the cholesterol liberated from LDL degradation must be reused.